Determinants of Premature Deindustrialization and Uneven Manufacturing Industry in Indonesia - Imantria, Benny (Jurnal Penelitian Ekonomi dan Bisnis, 2025)
Indonesia is currently undergoing an economic transformation to become a developed country, but premature deindustrialization and uneven manufacturing industry between western and eastern Indonesia may hinder economic development. This study aims to identify determinants of Indonesia's declining manufacturing industry output, which has led to premature deindustrialization and uneven manufacturing industry. Data sample used is a panel dataset of 34 provinces during the period 2015-2023 which was analyzed using panel data regression and spatial autoregressive combined (SAC). The novelty of this study lies in production function perspective and spatial regression. This study finds that foreign direct investment, domestic investment, labor, and trade openness have a significant positive effect on manufacturing industry output, while average years of schooling and minimum wage have no significant effect on manufacturing industry output in Indonesia. In addition, there is no significant spillover effect from neighboring provinces that determines manufacturing industry output in Indonesia during the observation period. Policymakers are expected to increase value and investment projects, employment opportunities, formal education quality, capital goods imports, and final goods exports. In addition, minimum wage needs to be adjusted according to regional conditions and provide employment affirmation to local labor.